Memorable tourist experience, service quality, and revisit intention: strategies for strengthening sustainable tourism at Kebumen Geopark - Rahmawati, Esti Dwi; Setiyani, Rahmawati (Institute of Computer Science (IOCS), 2025)
Sustainable tourism is a strategic issue that is not only oriented towards economic growth, but also environmental sustainability and cultural preservation. This study aims to analyze the influence of memorable tourist experience (MTE) and service quality on tourist satisfaction and revisit intention. The method used is a mixed methods with a sequential explanatory design, combining quantitative analysis using SEM-PLS and a qualitative approach through in-depth interviews. The results show that MTE has a positive and significant effect on tourist satisfaction and revisit intention. Service quality is proven to have a significant effect on satisfaction, but not a significant effect on revisit intention. In addition, tourist satisfaction has a significant positive effect on revisit intention and acts as a mediating variable in both the relationship between MTE and service quality on revisit intention. Practically, the results of this study can be a reference for destination managers in strengthening the strategy for managing the Kebumen Geopark sustainably.